PENGEMBANGAN PARIWISATA BERBASIS KOMUNITAS PESISIR DAN DAMPAKNYA TERHADAP EKONOMI LOKAL: STUDI KASUS PANTAI BIMO, BANYUWANGI - Aminulloh, Aminulloh; ImamSyafi’i; Ni Kade Juli Rastitiati3; Bungon Sawatsuk; Wildana M. Giffari (Pusat Penelitian dan Pengabdian Kepada Masyarakat Politeknik Pariwisata Bali, 2026)
This study scrutinizes how the community has responded to the development of Bimo Coastal Tourism, Banyuwangi Regency, East Java, Indonesia, utilizing a framework of Community-Based Tourism. Addressing the absence of village-based, community-driven coastal tourism, this research uses a qualitative research approach by conducting observations, in-depth interviews, and document analysis from local communities, tourism managers, and village authorities. The study discovers that the genesis of Bimo Beach development was from bottom-up initiatives driving social cohesion, informal governance, and environmentally friendly practices rather than large-scale investment. Local tourism-related activities generated actual economic impacts with the induced benefits reaching the households, mainly in the trade and service sectors. Earnings from petty trade and parking services diversified livelihoods and built community resilience. The case identifies that local government can become a big brother by congregation strengthening community institutions, incorporating into tourism planning the element of environmental conservation, and enforcing a light-touch regulatory frameworks to monitor, evaluate, and standardize services. This policy model can be useful for other emerging coastal tourism destinations in Indonesia sharing similar socio-cultural and environmental features.